Rational approaches to the treatment of hypertension: drug therapy—monotherapy, combination, or fixed-dose combination? - Canbakan, Başol (Nature Publishing Group, 2013)
Blood pressure (BP) control is inadequate worldwide. Many clinical trials suggest that BP is not satisfactorily controlled using monotherapy in most patients. Free drug or fixed-dose combinations are other therapeutic options. The advantages and disadvantages for different treatment approaches are discussed in this review.